FREQUENCY GENERATOR DEMONSTRATION USING HALF MODE SUBSTRATE INTEGRATED WAVEGUIDE (SIW) STRUCTURES FOR CHIPLESS RADIO FREQUENCY IDENTIFICATION (RFID) READER - Sharma, Vijay; Hashmi, Mohammad (IET Circuits, Devices & Systems, 2022)
A frequency generator based on the forward coupler principle is proposed. The proposed design, intended for high-frequency applications, uses Half-Mode Substrate Integrated Waveguide structure to realise the forward coupler. It thus achieves compactness, requiring approximately half the area compared to Substrate Integrated Waveguide structures, and supports non Transverse Electromagnetic (TEM) functionality. The non-TEM environment provides the flexibility to use the frequency generator for chipless Radio Frequency Identification readers in the sub-GHz band and mm-wave range. Full-wave simulations and the subsequent measurements on a prototype developed on Rogers 3006 substrate performed for the forward coupler resonators and frequency generator validate the proposed design concept.
Keywords: Type of access: Open Access; Substrate Integrated Waveguide; Radio Frequency Identification (RFID) reader